Sasha and Emma : the anarchist odyssey of Alexander Berkman and Emma Goldman - Avrich, Paul (Belknap Press of Harvard University Press, 2012)
In 1889 Emma Goldman and Alexander Berkman met in a Lower East Side coffee shop. Over the next fifty years they became fast friends, fleeting lovers, and loyal comrades. This dual biography offers a glimpse into their intertwined lives, the influence of the anarchist movement they shaped, and their unyielding commitment to equality and justice.